Variables associated with occupational poisoning by agricultural pesticides, in the west mesoregion of Paraná, from 2010 to 2020 (Research, Society and Development, 2022)
Pesticides represent a great risk to the health of workers. The objective of this work was to verify the cases reported in the SINAN of occupational poisoning by agricultural pesticides in the western mesoregion of the State of Paraná, from 2010 to 2020. In order to quantify the incidence, as well as relate it to several variables, in order to understand the factors and risks associated with the health of the exposed working population. This is a survey of the number of cases of laboral poisoning by pesticides in the western mesoregion of the state of Paraná, in the period from 2010 to 2020, through the notifications made available in DATASUS. In addition, the following variables were analyzed: age groups, education, sex, circumstances, type of exposure, case evolution, microregions and year of notification. 450 cases of occupational poisoning by agricultural pesticides were reported in the western mesoregion of Paraná, with the microregion of Cascavel having the highest number of notifications. Of the total, most were male, aged 20 to 59 years, with incomplete primary education. There was still a prevalence of acute exposure, with evolution to cure without sequelae. The diagnosis was predominantly made by clinical-epidemiological means, without laboratory confirmation.